2012
DOI: 10.1007/s10803-012-1685-7
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and Predictors of Anxiety Among Siblings of Children with Autism Spectrum Disorders

Abstract: The purpose of this study was to examine patterns of anxiety among siblings of children with autism spectrum disorders (ASD), and determine the characteristics of the child with ASD and their parents that predicted anxiety. Data was collected from 1755 siblings of children with ASD whose families participated in the Simons Simplex Collection; siblings ranged in age from 3 to 18 years (M=9 years). Male siblings were at increased risk for sub-clinical anxiety problems during middle childhood. Parental history of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
1
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 56 publications
6
41
1
3
Order By: Relevance
“…That is, CBP were found to positively predict siblings' total CDI-2 scores. That CBP might affect psychological outcomes such as depression in siblings of children with a DD has also been observed in other recent studies (Mayer et al, 2011;Shivers et al, 2012). These findings might have implications for the design and delivery of psychotherapeutic interventions.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…That is, CBP were found to positively predict siblings' total CDI-2 scores. That CBP might affect psychological outcomes such as depression in siblings of children with a DD has also been observed in other recent studies (Mayer et al, 2011;Shivers et al, 2012). These findings might have implications for the design and delivery of psychotherapeutic interventions.…”
Section: Discussionsupporting
confidence: 70%
“…These findings resonate with studies involving parental caregivers of children with a DD, where CBP were found to account for much of the variance in caregivers' feelings of depression (Gallagher et al, 2008;Lovell, Moss, & Wetherell, 2015). Most recently, in a study involving siblings of children with ASD, Shivers, Deisenroth and Taylor (2012) found that CBP, along with maternal stress, uniquely predicted siblings' feelings of anxiety. Perceived availability of social support has also been shown to be influential for the psychological adjustment of siblings of children with a DD.…”
Section: Introductionsupporting
confidence: 73%
“…We know much less about factors that explain within-group variations in the experiences of TDSib-ASDSib dyads. Although factors such as parentsā€™ mental health, parenting stress, and social support have been studied as correlates, mediators and moderators of the links between experiences with ASDSibs and TDSibsā€™ adjustment (Hastings, 2003; Orsmond & Seltzer, 2009; Shivers et al, 2013; Sikora, Moran, Orlich, Hall, Kovacs, Delahaye, Clemons, & Kuhlthau, 2013), we found no studies that investigated parent-child relationship correlates of TDSib-ASDSib relationship behaviors . Further, beyond research on parentsā€™ differential treatment of siblings, discussed in the following section, we found no studies of parenting directed at the TDSib-ASDSib dyad .…”
Section: Theoretical Perspectives On Sibling Relationship Behaviorsmentioning
confidence: 84%
“…Relationships of ASDSibs have been described as generally positive; they also may involve less conflict, but less warmth and involvement than those of typically developing siblings (Kaminsky & Dewey, 2001; McHale, Sloan, & Simeonsson, 1986; Orsmond, Kuo & Seltzer, 2009) and distress in response to the ASDSibā€™s aggressive and disruptive behaviors (Mascha & Boucher, 2006). With respect to adjustment, youth with ASDSibs are generally well-adjusted and some may benefit from their experiences in their social competencies and self concept (Kaminsky & Dewey, 2002; Macks & Reeve, 2007; Pilowsky, Yirmiya, Doppelt, Gross-Tsur, & Shalev, 2004; Verte, Roeyers & Buysse, 2003), but there also is evidence of adjustment problems in TDSibs (Hastings, 2003; Shivers, Deisenroth, & Taylor, 2013). Reviews target research designs and methods as a basis for inconsistencies across studies (Hodapp, Glidden & Kaiser, 2005; Meadan et al, 2010): Small sample sizes, samples of convenience, inattention to family structure, samples that differ in comparison group, age, and data sources mean that it is difficult to compare results across studies.…”
mentioning
confidence: 99%
“…Parents of children with ASD and comorbid symptoms are not the only ones affected with psychological symptoms. Shivers et al (2013) investigated sibling well-being. Parental history of anxiety and sibling (with ASD) behavior problems predicted sibling anxiety.…”
Section: Relationships Between Comorbid Psychopathology In Asd and Otmentioning
confidence: 99%